Teacher Certification Allowance in Islamic Economic Perspective - Rosmawati; Abustani Ilyas; Syaharuddin; Rahmawati Muin (CV ODIS, 2022)
This study examines the process of obtaining teacher certification allowance, the implementation of certification allowances for the teacher, and the implications of teacher certification allowances from an Islamic economics view. The study followed a qualitative-descriptive research method with the researcher as the main instrument. The selection of the research sample was through the purposive sampling technique. Data were obtained through observation, interviews, and documentation which were then analyzed using interaction analysis techniques. There are three main findings in this study. First, teacher certification allowance was obtained through three channels: the education path with the Direct Provision of Educator Certificates (PSPL), the teacher functional path with the portfolio (PF), and the PLPG and PPG training pathways. Second, the implementation of teacher certification allowances in the perspective of Islamic economics, in general, has gone according to expectations. However, the essential goal of the certification program, namely increasing teacher competence, was secondary to some teachers. Third, teachers who receive certification allowances did not think that the income earned was entirely for themselves; some are for individual, family needs, and in the manner for Allah